Strengthening School Culture-Based Character Education at SMAN 2 Sukabumi - Nur Ainiyah; Rachmat Mulyana; Ida Nursida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The development of science and technology, various conditions in society are changing. The noble values that became the legacy slowly faded away. This change has underpinned the pattern of Community life not only in adults but also the order of life of students. The condition of character is eroded into mutual concern, good manners, honesty, noble morals, replaced by conditions of violence, behavior that violates and is contrary to religious values, norms and customs that apply in society. Strengthening character education is one solution to strengthen school culture. This research emphasizes the implementation of strengthening school culture-based character education at SMAN 2 Sukabumi. The method used in this research is a qualitative method with an ethnographic approach. Data collection techniques with observation, interviews and documentation. The research results show that to carry out school culture-based character education at SMAN 2 Sukabumi there are strategic policies, superior culture and superior school programs.